2013
DOI: 10.2190/ec.49.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Paper-and-Pencil Programming Strategy toward Computational Thinking for Non-Majors: Design Your Solution

Abstract: The paper-and-pencil programming strategy (PPS) is a way of representing an idea logically by any representation that can be created using paper and pencil. It was developed for non-computer majors to improve their understanding and use of computational thinking and increase interest in learning computer science. A total of 110 non-majors in their sophomore year were assigned to either a Logo or a PPS course with attendance being 2 hours per week for 15 weeks. To measure the effectiveness of PPS, the Group Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 47 publications
(48 reference statements)
1
37
0
2
Order By: Relevance
“…It was considered that this was due to the perception that CT was associated with computer sciences (Israel, Pearson, Tapia, Wherfel, & Reese, 2015; B. Kim, T. Kim, & J. Kim, 2013;Pellas & Peroutseas, 2016), although it was stated in the literature that CT is a skill for all, not only for those who are computer science professionals (Willamon, 2016;Wing, Henderson, Hazzan, & Cortina, 2005). This finding was consistent with Özcınar's (2017) claim that CT studies were predominantly published in computer science resources.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered that this was due to the perception that CT was associated with computer sciences (Israel, Pearson, Tapia, Wherfel, & Reese, 2015; B. Kim, T. Kim, & J. Kim, 2013;Pellas & Peroutseas, 2016), although it was stated in the literature that CT is a skill for all, not only for those who are computer science professionals (Willamon, 2016;Wing, Henderson, Hazzan, & Cortina, 2005). This finding was consistent with Özcınar's (2017) claim that CT studies were predominantly published in computer science resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the findings of the current study, majority of the studies on CT in the literature concentrated on education and technology. Furthermore, study findings demonstrated that CT was mostly discussed based on computer technologies (Israel et al, 2015;Kim, Kim, & Kim, 2013;Pellas & Peroutseas, 2016). It was considered that this finding was due to the low level of perception of the significance of CT in other fields.…”
Section: Conclusion and Recommendations For Future Researchmentioning
confidence: 99%
“…We often observed that students started programming without a clear plan and tinkered with code blocks by trial and error. We suggest that students need to learn how to sketch out their story, and that it should be the first step to design a program after learning the core concepts of programming (Kim, Kim, & Kim, 2013). Instructional strategies for planning, such as creating a story synopsis or storyboard by writing or drawing, can be adopted (Brennan & Resnick, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the elaboration theory advocates (Reigeluth, 1999), students need to practice simple tasks involving a specific reasoning skill earlier. Also, a condition chart or pseudo code could aid with logical reasoning to structure decomposed tasks and determine relevant conditions (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%